Matemática
queremjuju
5

Determine f(0), f(1), f(2), f(3), f(4), e f(-1) das seguintes funções : A) f (x) = 2x+4 B) f (x) = 3x+1 C) f (x) = -2x+2 C) f (x) = x-4 E) f (x) = 3x-5

+0
(1) Respostas
Leilla10

basta substituir: LETRA A: [latex]f(x) = 2x + 4[/latex] [latex]f(0) = 2*(0) + 4 = 4[/latex] [latex]\boxed{f(0)=4}[/latex] [latex]f(1) = 2*(1) + 4 = 2 + 4 = 6[/latex] [latex]\boxed{f(1)=6}[/latex] [latex]f(2) = 2*(2) + 4 = 4 + 4 = 8[/latex] [latex]\boxed{f(2)=8}[/latex] [latex]f(3) = 2*(3) + 4 = 6 + 4 = 10[/latex] [latex]\boxed{f(3)=10}[/latex] [latex]f(4) = 2*(4) + 4 = 8 + 4 = 12[/latex] [latex]\boxed{f(4)=12}[/latex] [latex]f(-1) = 2*(-1) + 4 = -2 + 4 = 2[/latex] [latex]\boxed{f(-1)=2}[/latex] Idem para as outras letras. Abraço!

Adicionar resposta